Distribution of some active elements in primary graphite precipitates. (3rd March 2016) - Theuwissen, K.; Duguet, T.; Esvan, J.; Lacaze, J.
Abstract : The distributions of cerium and oxygen in the matrix and in graphite precipitates of a pure Fe–C–Ce cast iron sample have been studied using scanning Auger microscopy. It is shown that there is no accumulation of any element at the graphite-matrix interface. Cerium was detected in some cases in spheroidal graphite precipitates, most often associated with oxygen. Various non-spheroidal graphite precipitates proved to contain cerium and oxygen suggesting a correlation between cerium content and graphite degeneracy.